Revision of the polytypic electric fish Gymnotus carapo (Gymnotiformes, Teleostei), with descriptions of seven subspecies - Craig, Jack M.; Crampton, William G. R.; Albert, James S. (Zootaxa, 2017)
The banded knife fish Gymnotus carapo is among the most widely distributed, broadly adapted (eurytopic), and phenotypically variable fish species in South America, with a geographic range of about 14 million km2, from the Llanos of Venezuela to the Pampas of northern Argentina. Here we assess the structure of phenotypic variation in G. carapo across this vast range from a study of 486 specimens representing the G. carapo clade, including 175 specimens of G. carapo collected from across the continental platform. We use multivariate statistics to quantify phenotypic differences within and among subspecies and species in aspects of pigmentation, caliper-based morphometrics, geometric morphometrics, meristics, and osteology. Our results demonstrate significant, but not diagnostic, differences among specimens representing seven new subspecies: G. c. australis from the La Plata (Paraná-Paraguay) basin, G. c. caatingaensis from the Parnaíba basin in the Brazilian state of Piauí, G. c. carapo from Suriname and French Guiana, G. c. madeirensis from the upper Madeira basin, G. c. occidentalis from the western Amazon, Negro, and Essequibo basins, G. c. orientalis from the eastern Amazon, Tocantins and Trombetas basins, and G. c. septentrionalis from the Orinoco basin and Trinidad Island. These results support the use of the subspecies, but not the species, rank to recognize and name these regionally delimited taxonomic entities.